Efektywność wybranych metod uzupełniania informacji niekompletnych a różne mechanizmy powstawania braków danych - Grabowski, Mariusz (Efficiency of Selected Methods for Imputation of Incomplete Data and Different Missing Data Mechanisms, 2005)
Incomplete data, issue addressed by various authors, constitute a serious problem for many classical data analysis methods. The concept of utilizing SOM neural network (Kohonen 1995) as an effective technique for handling data vectors containing missing components was presented in the previous papers of the author. The following article compares SOM with other advanced missing data handling methods across different missing data mechanisms (Little, Rubin 1987): MCAR, MAR and NMAR. Artificially created multidimensional random data sets with various predefined distributions will be the basis for this comparison.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 471-477